ZOOMORPHIC MOTIFS ON POLYCHROME GLAZED CERAMICS OF THE SELJUK PERIOD (Based on the materials of Ganja and Shamkir) - Dostiev, Tarih Mejrut ogly (History, Archeology and Ethnography of the Caucasus, 2023)
As a result of archaeological excavations at the medieval sities Old Ganja and Shamkir, located in the western region of the Republic of Azerbaijan, a large collection of glazed ceramics was revealed. The artistic design of the glazed ceramics of the Seljuk period  differs significantly from the ceramics of the early Islamic period in its decoration techniques, rich ornament, originality of the plot composition. Highly artistic glazed polychrome ceramics with figurative motifs stand out, which is an irrefutable material source for determining the high professionalism and delicate taste of local ceramists. This article provides a systematization and detailed analysis of the collection of glazed polychrome ceramics of the Seljuk period with images of animals, represented mainly by open-shaped tableware. These ceramic artifacts are interpreted as examples of arts and crafts. These products are decorated with engraving and polychrome coloring under the colorless, transparent glaze. Generally, zoomorphic images are  combined with floral, geometric and epigraphic ornaments. The polychrome ceramics of this period are characterized by a color scheme based on three colors. Both domestic and wild animals are depicted. The images or motifs of animals were obviously associated with various animistic and totemic ideas.
Keywords: Old Ganja; Shamkir; Middle Ages; glazed ceramics; decor; zoomorphic motifs.